2023
DOI: 10.1002/cmdc.202200468
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic‐Targeted Nano‐enzyme with Resveratrol Loading for Precise Relief of Nonalcoholic Steatohepatitis

Abstract: Nonalcoholic steatohepatitis (NASH) is characterized by massive lipid deposition in hepatocytes and is often associated with hepatic inflammation and other severe metabolic syndromes. The intervention of NASH can prevent its further progression into hepatocarcinoma. In this study we have successfully constructed liver‐targeted Ce‐based hollow mesoporous nanocarriers loaded with bioactive drugs. This may provide an effective approach for eliminating NASH. Liver‐section‐specific targeting was realized by covalen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…Resveratrol (3,5,4-trihydroxy-trans-stilbene, Res) is a natural polyphenol found in plants such as peanuts, grapes, and strawberries [ 9 , 10 ]. Recently, many studies have reported that Res possesses anti-inflammatory, anti-cancer, and anti-bacterial properties [ 11 , 12 , 13 ]. Intriguingly, the ability of Res to induce antioxidant formation in many cell types has validated its anti-aging potential, which has, in turn, attracted extensive attention in the research community.…”
Section: Introductionmentioning
confidence: 99%
“…Resveratrol (3,5,4-trihydroxy-trans-stilbene, Res) is a natural polyphenol found in plants such as peanuts, grapes, and strawberries [ 9 , 10 ]. Recently, many studies have reported that Res possesses anti-inflammatory, anti-cancer, and anti-bacterial properties [ 11 , 12 , 13 ]. Intriguingly, the ability of Res to induce antioxidant formation in many cell types has validated its anti-aging potential, which has, in turn, attracted extensive attention in the research community.…”
Section: Introductionmentioning
confidence: 99%
“…were established for the treatment of NASH mice, and the results demonstrated increased resveratrol delivery to the liver, reduced lipid buildup, and enhanced anti-inflammatory activity (Tong et al, 2023).…”
Section: Nano-delivery System Of Polyphenols In Liver Diseasesmentioning
confidence: 99%
“…This nanocarrier effectively alleviated lipid buildup and insulin resistance by modulating the AMPK/SIRT1/FAS/SREBP1c signaling pathway (Teng et al, 2019). Furthermore, similar resveratrol nanocarriers (resveratrol‐CeO2‐ galactose) were established for the treatment of NASH mice, and the results demonstrated increased resveratrol delivery to the liver, reduced lipid buildup, and enhanced anti‐inflammatory activity (Tong et al, 2023). Moreover, curcumin complexes with silver nanoparticles (AgNPs) were developed for the treatment of CCl4‐induced hepatic fibrosis.…”
Section: Nano‐delivery System Of Polyphenols In Liver Diseasesmentioning
confidence: 99%
“…As well as protecting cells from oxidative stress, resveratrol also promotes the expression of antioxidative enzymes and their substrates ( Miguel et al, 2021 ; Santos et al, 2021 ). Recently, it has been suggested that resveratrol has hepatoprotection properties through its anti-inflammatory and antioxidant effects ( Chupradit et al, 2022 ; Ma et al, 2022 ; Tong et al, 2022 ). It has also been reported that resveratrol attenuates acetaminophen toxic metabolite N-acetyl-p-benzoquinone-imine and facilitates liver regeneration by modulating the silent mating type information regulation two homolog (SIRT1), tumor protein P53, and Tumor Necrosis Factor-alpha (TNF-α) ( Sener et al, 2006 ; Wang et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%